Early Strength Development of Soft Clay Stabilized by One-Part Ground Granulated Blast Furnace Slag and Fly Ash-Based Geopolymer - Zheng, Xiyao; Wu, Jun (Frontiers in Materials, 2021)
Abstract: One-part or "just add water" geopolymer is a cementitious material, which is friendly to environment and user in application. However, the mechanical behavior of the soft soil stabilized by one-part geopolymer is not well acknowledged. In this study, soft clay was stabilized with ground granulated blast furnace slag (GGBFS) and fly ash (FA) based geopolymer that was a mixture of solid aluminosilicate precursor (Al-Si raw materials: GGBFS and FA), solid alkali-activator and water. The objective was to adopt one-part geopolymer as an alternative soil binder to completely replace ordinary portland cement (OPC) for stabilizing the soft clay and evaluate the effect of the factors (i.e. GBFS/FA ratio in Al-Si precursor, activator/Al-Si precursor ratio, and water/binder ratio) that influenced the early strength. Results showed that the increasing of the FA content in the Al-Si precursor increased the unconfined compressive strength (UCS) values significantly through the geopolymerization process. The highest UCS values were achieved with 90% GGBFS to 10% FA in precursor when the activator/precursor and water/binder ratio is 0.15 and 0.7, respectively. The UCS values of geopolymer stabilized clay could reach 1.5 MPa at 14 days at ambient temperature, which is much higher than that of OPC stabilized clay. The UCS values decreased when the FA content beyond 10% in the precursor. The microstructure and mineralogy analyses indicated that the prolific hydration products like calcium silicate hydrate (C-S-H), calcium aluminum hydrate (C-A-H) and calcium aluminum silicate hydrate (C-A-S-H), which contributed greatly to strengthen the soft clay by forming the soil skeleton and infilling among clay particles, while Sodium aluminosilicate (N-A-S-H) gel is only served to fill the part of porosities in the soil and cannot effectively result to enhancement the UCS values of the one-part geopolymer stabilized soft clay. This paper results suggested that one-part GGBFS-FA based geopolymer have the potential to replace OPC in the manufacture of stabilized soft clay.